2022
DOI: 10.1371/journal.pone.0269124
|View full text |Cite
|
Sign up to set email alerts
|

Translating a theory-based positive deviance approach into an applied tool: Mitigating barriers among health professionals (HPs) regarding infection prevention and control (IPC) guidelines

Abstract: Background Although a wide range of intervention programs and methods have been implemented to increase health professionals’ (HPs) adherence with infection prevention and control (IPC) guidelines and decrease the incidence of healthcare associated infections (HAIs), a significant discrepancy remains between the guidelines and their implementation in practice. Objectives This study proposes an applied tool based on the integrated theoretical framework of the positive deviance (PD) approach for developing mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Therefore, we saw great importance in the methodological applied expansion we conducted in our study, which can allow for more detailed insights into the study quality and degree of intervention implementation. A detailed description of the intervention methodology, with its applied steps and tools, may greatly assist researchers and professionals implementing similar studies in a variety of healthcare settings ( 12 ). This point was also raised in the article by Zingg et al ( 29 ) which presents the conclusions of 42 experts from the IPC field [Geneva infection prevention and control (IPC) – think tank 2017) who came together to develop an IPC vision, a plan on how to prevent antimicrobial resistance (AMR), and to agree on a road map for research and public health activities.…”
Section: Challenge 4: How To Translate the Pd Approach Into An Applie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we saw great importance in the methodological applied expansion we conducted in our study, which can allow for more detailed insights into the study quality and degree of intervention implementation. A detailed description of the intervention methodology, with its applied steps and tools, may greatly assist researchers and professionals implementing similar studies in a variety of healthcare settings ( 12 ). This point was also raised in the article by Zingg et al ( 29 ) which presents the conclusions of 42 experts from the IPC field [Geneva infection prevention and control (IPC) – think tank 2017) who came together to develop an IPC vision, a plan on how to prevent antimicrobial resistance (AMR), and to agree on a road map for research and public health activities.…”
Section: Challenge 4: How To Translate the Pd Approach Into An Applie...mentioning
confidence: 99%
“…To handle this challenge, we translated the positive deviance approach to an applied methodological tool, proposing step-by-step actions to mitigate barriers and minimize the existing ambiguity between the written guidelines to the work in the field, among HPs. The methodological tool is used as tool kit to find applicable solutions for each barrier identified through interviews, focus groups, and observations, to promote the use of PD practices that are not found in the official IPC guidelines ( 12 ).…”
Section: Challenge 4: How To Translate the Pd Approach Into An Applie...mentioning
confidence: 99%
“…For instance, among the low-income countries studied, only nine (45%) indicated having a national IPC program, four (20%) guidelines on implementation methods, and one (5%) monitored compliance with IPC practice (5). The global assessment showed that more efforts are needed to strengthen IPC strategies in low-income countries susceptible to disease outbreaks such as COVID-19 and tuberculosis (12).…”
Section: Introductionmentioning
confidence: 99%